An Assessment of Managerial Skills in the Labour Intensive Industry: A Case Study of a Garments Manufacturing Firm - Hossan, Chowdhury Golam; Sarker, Md. Atiqur Rahman; Afroze, Rumana (JABM, 2012)
RMG sector in Bangladesh is booming in recent times with competitive advantage and profitability through exports. But this sector is facing challenge in achieving management efficiency which leads to experience disputes and violent protests by the labours at present. This is also because of the absence of managerial skills in the organisations of RMG sector in Bangladesh. In order to remain competitive in global market and to achieve higher organisational performance, special emphasis should be given to develop the managerial skills. This study has been conducted to assess the some selected managerial skills among mid-level managers in the RMG sector of Bangladesh. Seven managerial skills were selected for this study. Findings reveal that managers need capacity building in some key management skills.